A renewed call for transdisciplinary action on NCDs - Brigit Toebes; Marlies Hesselman; Jochen O. Mierau; Jitse P. van Dijk (BMC, 2020)
Abstract Notwithstanding COVID-19, non-communicable diseases (NCDs) will be the leading cause of death in every region in the world by 2030. This contribution, which forms an introduction to our collection of articles in this journal, identifies elements for a transdisciplinary research agenda between law, public health, health economics and international relations aimed at designing concrete interventions to curb the NCD pandemic, both globally and domestically.